Comparison of cervical cancer screening by visual inspection with acetic acid versus cervical-cytology in pregnancy - Shamsunder, Saritha; Pannu, Deepika; Khanna, Geetika; Banerjee, Ananya; Zutshi, Vijay; Malik, Sunita (Indian Journal of Medical and Paediatric Oncology, 2019)
Aims: The aim of this study was to compare visual inspection with acetic acid (VIA) with cervical cytology for cervical cancer screening in pregnant women. Settings and Design: A prospective cohort study was conducted after institutional ethical committee approval in a tertiary care hospital in Northern India. Pregnant women of gestational age <28 weeks were randomly recruited from the antenatal clinic. Subjects and Methods: All eligible women had a Pap smear followed by VIA; colposcopy was performed if either test was positive. Swede score was used for grading of the acetowhite lesion; biopsy was planned if Swede score was ≥8. Statistical Analysis Used: The sensitivity, specificity, and predictive values for both screening methods were compared with colposcopy as the reference standard. Results: There were 370 low-risk pregnant women in the age group of 20–36 years in the study with a mean parity was 2.1, and the median period of gestation of 14.6 weeks. Abnormal Pap cytology was seen in 5.9% (n = 22) of patients; the abnormalities were ASCUS in 13 (59%), LSIL in 4 (18.2%), and AGC-NOS in 5 (22.7%) patients. VIA positivity was found in 8.4% (n = 31). The positive predictive value was 31.8% for cervical cytology and 48.4% for VIA (P = 0.001). No invasive lesion was detected. Positive predictive value of VIA was significantly higher than Pap cytology for detection of abnormal lesions. Conclusions: VIA is a cost-effective method with better predictive value than Pap smear for cervical cancer screening in pregnant women.
Keywords: Cervical cancer screening; cervical cytology; pregnancy; visual inspection with acetic acid